2003
DOI: 10.1021/ic035020r
|View full text |Cite
|
Sign up to set email alerts
|

Photochromism of Metal Complexes Composed of Diarylethene Ligands and Zn(II), Mn(II), and Cu(II) Hexafluoroacetylacetonates

Abstract: Metal complexes composed of bidentate 1,2-bis(2-methyl-5-(4-pyridyl)-3-thienyl)perfluorocyclopentene (1a) and monodentate 1-(2-methyl-5-phenyl-3-thienyl)-2-(2-methyl-5-(4-pyridyl)-3-thienyl)perfluorocyclopentene (2a) photochromic ligands and M(hfac)(2) (M = Zn(II), Mn(II), and Cu(II)) were prepared, and their photoinduced coordination structural changes were studied. X-ray crystallographic analyses showed the formation of coordination polymers and discrete 1:2 complexes for bidentate and monodentate ligands, r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
31
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 86 publications
(31 citation statements)
references
References 34 publications
0
31
0
Order By: Relevance
“…A flexible porous crystal was prepared using a photochromic module, a bis(pyridyl)dithienylethene ( L O ) 36, 37 that shows a highly effective interconversion between open- ( L O ) and closed-ring ( L C ) isomers (Fig. 1) in various solvents (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…A flexible porous crystal was prepared using a photochromic module, a bis(pyridyl)dithienylethene ( L O ) 36, 37 that shows a highly effective interconversion between open- ( L O ) and closed-ring ( L C ) isomers (Fig. 1) in various solvents (Supplementary Fig.…”
Section: Resultsmentioning
confidence: 99%
“…[12] Thec rystal structures of one coordination compound from L H [13] and five coordination compounds from L F [10,14] have been reported so far,but none of them with platinum as metal. [12] Thec rystal structures of one coordination compound from L H [13] and five coordination compounds from L F [10,14] have been reported so far,but none of them with platinum as metal.…”
mentioning
confidence: 99%
“…Results suggested that no complex was formed between 2a or 2b with Cu 2+ , and the binding site occurred at O atom instead of at S and N atoms. The complex Cu–1a is probably formed48 by binding two Cu 2+ with two phenol units, which prefers to the photocyclization of diarylethene due to the increase of the anti‐parallel conformation 49, 50…”
Section: Resultsmentioning
confidence: 99%